ANALISIS PENGARUH KINERJA ANGKUTAN UMUM TRANS SARBAGITA TERHADAP ANIMO MASYARAKAT PENGGUNA DI PROVINSI BALI - Nirjaya, A.A. Gd Oka; Setiawina, I Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.08. TAHUN 2016, 2016)
Bali Provincial Government has been providing public transport Trans Sarbagita which aims to reduce the use of private vehicles, congestion and facilitate economic activities. This study aimed to analyze the influence of the dimensions of the vehicle, the attitude of the vehicle crews and freight rates to transport performance Trans Sarbagita, to analyze the influence of the dimensions of the vehicle, the attitude of the vehicle crew, transport fares and freight performance Trans Sarbagita against public interest, and to analyze the dimensions of the vehicle, the attitude of the vehicle crews and freight rates affect the interest of the public transport users through the performance Trans Sarbagita. The analysis technique used is path analysis with SPSS. The results showed that the dimensions of the vehicle, the attitude of the vehicle crews and transport fares positive and significant impact on the performance of transport Trans Sarbagita. The dimensions of the vehicle , vehicle crews attitude , the freight rates and the performance of transport Trans Sarbagita positive and significant impact on the public interest. The dimensions of the vehicle, the attitude of the vehicle crews and freight rates affect the interest of the public transport users through the performance Trans Sarbagita.
Keywords: vehicle size, the attitude of the vehicle crew, freight rates, the performance of transport Trans Sarbagita, the public interest